On-line hyphenation of solid-phase extraction to chromatographic separation of sulfonamides with fused-core columns in sequential injection chromatography - Batista, Alex D; Chocholouš, Petr; Satínský, Dalibor; Solich, Petr; Rocha, Fábio R P (Talanta, 2015)
On-line sample pretreatment (clean-up and analyte preconcentration) is for the first time coupled to sequential injection chromatography. The approach combines anion-exchange solid-phase extraction and the highly effective pentafluorophenylpropyl (F5) fused-core particle column for separation of eight sulfonamide antibiotics with similar structures (sulfathiazole, sulfanilamide, sulfacetamide, sulfadiazine, sulfamerazine, sulfadimidine, sulfamethoxazole and sulfadimethoxine). The stationary phase was selected after a critical comparison of the performance achieved by three fused-core reversed phase columns (Ascentis(®) Express RP-Amide, Phenyl-Hexyl, and F5) and two monolithic columns (Chromolith(®) High Resolution RP-18 and CN). Acetonitrile and acetate buffer pH 5.0 at 0.60 mL min(-1) were used as mobile phase to perform the separations before spectrophotometric detection. The first mobile phase was successfully used as eluent from SPE column ensuring transfer of a narrow zone to the chromatographic column. Enrichment factors up to 39.2 were achieved with a 500 µL sample volume. The developed procedure showed analysis time <10.5 min, resolutions >1.83 with peak symmetry ≤1.52, LODs between 4.9 and 27 µg L(-1), linear response ranges from 30.0 to 1000.0 µg L(-1) (r(2)>0.996) and RSDs of peak heights <2.9% (n=6) at a 100 µg L(-1) level and enabled the screening control of freshwater samples contaminated at the 100 µg L(-1) level. The proposed approach expanded the analytical potentiality of SIC and avoided the time-consuming batch sample pretreatment step, thus minimizing risks of sample contamination and analyte losses.
Keywords: Chromatography, High Pressure Liquid; Limit of Detection; limita detekce; průtoková injekční analýza; SPE-SIC; F5; extrakce na pevné fázi; Equipment Design; On-line SPE; Pentafluorophenylpropyl; sulfonamidy; řeky; antibakteriální látky; Rivers; Anti-Bacterial Agents; Flow Injection Analysis; Sequential Injection Chromatography; design vybavení; Solid Phase Extraction; Water Pollutants, Chemical; Fused core; vysokoúčinná kapalinová chromatografie; Sulfonamides; chemické látky znečišťující vodu; Anion-exchange